Phenols from Origanum dictamnus L. and Thymus vulgaris L. and their activity against Malassezia globosa carbonic anhydrase. Issue 6 (19th March 2022) - Paloukopoulou, Charikleia; Govari, Sofia; Soulioti, Athina; Stefanis, Ilias; Angeli, Andrea; Matheeussen, An; Capasso, Clemente; Cos, Paul; Supuran, Claudiu T.; Karioti, Anastasia
Abstract: Malassezia spp. are lipophilic fungi that are part of the normal flora of the human skin and are the etiological agents of dandruff and seborrheic dermatitis. β-Carbonic Anhydrases (CAs; EC 4.2.1.1) expressed from the pathogenic fungi are an alternative/complementary drug target. Previous work by our groups demonstrated that flavonoids and depsides can effectively inhibit Malassezia globosa β-CA (MgCA). In continuation of this study herein we report the inhibitory activity of a variety of phenols from Origanum dictamnus L. and Thymus vulgaris L. against β-MgCA, among them I4-II7-di-carvacrol, a new natural product. Structure elucidation of the compounds was performed by 1 D, 2 D NMR and spectrometric analyses. Xanthomicrol and rosmarinic acid were active in the (sub)micromolar range (KIS 0.6 and 2.2 μM, respectively vs 40.0 μM of the standard inhibitor acetazolamide). Finally, the compounds were not cytotoxic, but showed in vitro no activity against Malassezia furfur . GRAPHICAL ABSTRACT: